2018
DOI: 10.3390/coatings9010009
|View full text |Cite
|
Sign up to set email alerts
|

An All-Solid-State Electrochromic Device Based on WO3–Nb2O5 Composite Films Prepared by Fast-Alternating Bipolar-Pulsed Reactive Magnetron Sputtering

Abstract: In this study, WO3–Nb2O5 electrochromic films and an ITO/WO3–Nb2O5/Nb2O5/NiVOx/ITO all-solid-state electrochromic device were deposited using fast-alternating bipolar-pulsed magnetron sputtering using tungsten and niobium targets. The influence of different sputtering powers from the niobium target on the refractive index, extinction coefficient, optical modulation, coloration efficiency, reversibility, and durability of the WO3–Nb2O5 films is discussed. The aim of this work is to find the suitable Nb proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
9
2
Order By: Relevance
“…The electrochemical experiments were carried out by applying a voltage of −1.1 V for 5 seconds and of +0.5 V for 5 seconds and were carrying out for 4000 cycles for each potential value. It is observed that for all of the films, the stability was higher than that reported in a previous work 55,56 . This means that the films obtained by our method were robust and adhered strongly to the substrate.…”
Section: Resultscontrasting
confidence: 38%
See 1 more Smart Citation
“…The electrochemical experiments were carried out by applying a voltage of −1.1 V for 5 seconds and of +0.5 V for 5 seconds and were carrying out for 4000 cycles for each potential value. It is observed that for all of the films, the stability was higher than that reported in a previous work 55,56 . This means that the films obtained by our method were robust and adhered strongly to the substrate.…”
Section: Resultscontrasting
confidence: 38%
“…It is observed that for all of the films, the stability was higher than that reported in a previous work. 55,56 This means that the films obtained by our method were robust and adhered strongly to the substrate. Comparing the CA results obtained for different films, we found that the film annealed at 250 C showed the highest current density for both oxidized and reduced peaks.…”
Section: Electrochromic Full Cell Preparationmentioning
confidence: 85%
“…This reduction is reversible, and heating at 900 °C in air leads back to the yellowish and fully oxidized phase (Figure ). Like WO 3 , thin films of Nb 8 W 9 O 47 show electrochromatic behavior. …”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Among many transition metal oxides, tungsten (VI) oxide (WO 3 ) is attracting much attention. It has been used in electrochromic devices [16], gas sensors [17], electrocatalysis [18] and photoelectrocatalytic processes [19]. Recently, many studies have shown that WO 3 may be utilized as an energy storage material [20][21][22].…”
Section: Introductionmentioning
confidence: 99%